Vasorelaxant effects of ellagitannins isolated from Cuphea carthagenensis - Isla, Kaori Katiuska Yamaguchi; Tanae, Mirtes Midori; de Lima-Landman, Maria Teresa Riggio; de Magalhães, Pedro Melillo; Lapa, Antônio José; Souccar, Caden (Planta Medica, 2024)
Cuphea carthagenensis (Jacq.) J. F. Macbr. is a popular plant in Brazilian folk medicine owing to its hypotensive and central nervous system depressant effects. This study aimed to validate the hypotensive effect of the plantʼs aqueous extract (AE) in rats and examine the vascular actions of three hydrolyzable tannins, oenothein B, woodfordin C, and eucalbanin B, isolated from AE. Systolic blood pressure in unanesthetized rats was determined using the non-invasive tail-cuff method. Oral treatment of normotensive rats with 0.5 and 1.0 g/kg/day AE induced a dose-related hypotensive effect after 1 week. In rat aortic rings pre-contracted with noradrenaline, all ellagitannins (20 – 180 µM) induced a concentration-related vasorelaxation. This effect was blocked by either removing the endothelium or pre-incubating with NG-nitro-l-arginine methyl ester (10 µM), an inhibitor of nitric oxide (NO) synthase. In KCl-depolarized rat portal vein preparations, the investigated compounds did not affect significantly the maximal contractile responses and pD2 values of the concentration-response curves to CaCl2. Our results demonstrated the hypotensive effect of C. carthagenensis AE in unanesthetized rats. All isolated ellagitannins induced vasorelaxation in vitro via activating NO synthesis/NO release from endothelial cells, without altering the Ca2+ influx in vascular smooth muscle preparations. Considering the low oral bioavailability of ellagitannins, the determined in vitro actions of these compounds are unlikely to account for the hypotensive effect of AE in vivo. It remains to be determined the role of the bioactive ellagitannin-derived metabolites in the hypotensive effect observed after oral treatment of unanesthetized rats with the plant extract.
Keywords: Cuphea carthagenensis; Lythraceae; hypotension; ellagitannins; vasorelaxation; aortic rings